Exploring the entangled state and molecular weight of UHMWPE on the microstructure and mechanical properties of HDPE/UHMWPE blends. Issue 30 (18th March 2021) - Tao, Gan; Chen, Yuming; Mu, Jingshan; Zhang, Letian; Ye, Chunlin; Li, Wei
Abstract: Three types of ultra‐high molecular weight polyethylene (UHMWPE) with different entangled state and molecular weight were blended with high‐density polyethylene (HDPE) matrix by melt blending. Rheology, 2D‐SAXS, 2D‐WAXD, DSC, and mechanical tests were used to study the evolution and difference of microstructure and mechanical properties of the blends. The addition of weakly entangled UHMWPE enhanced the chain diffusion and chain orientation ability under a specific flow field. Thus, the rheological properties and mechanical properties of the blends were improved with the mix of weakly entangled UHMWPE. The mechanical properties enhancement effect of HDPE/UHMWPE blends with weakly entangled UHMWPE was owing to the shish‐kebab structure formed in the injection molding process. The molecular chains of UHMWPE with a low degree of entanglement and high molecular weight increased the lamella size and crystallinity of the blends during processing. This leads to the formation of more oriented shish structures and more kebab lamella. Besides, the molecular chains of weakly entangled UHMWPE were better interlocked and intertwined with other polyethylene chains in the amorphous region, acting as the tie molecules, significantly improving the impact resistance. Abstract : This study reveals the evolution and difference of microstructure and mechanical properties of the HDPE/UHMWPE blends with the molecular weight and the entangled state of UHMWPE.